ANALYSIS OF THE PROCESS STRATEGY IN CATFISH FARMING MITRA MAKMUR TULUNGAGUNG - Rafika Meilia Sari (Manajemen Bisnis, 2015)
The research aims is to determine time process duration of catfish cultivation. Processing chart used to analyse time determination in cultivation process. Processing chart shows a series of activities, operating time cycle, value-added time, and non value-added activities. The result shows that to produce 1 pool of catfish need 80 days with 1.5 eficiency level. Catfish size was standardized in harvest time and the farmer earn some profits.